Perception of a male midwife by Warsaw hospitals’ patients - Durka, Małgorzata; Goworek, Piotr; Cieśla, Beata; Cieśla, Paulina; Gotlib, Joanna; Cieślak, Halina (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Introduction. Midwifes were responsible for pregnant woman and those in childbirth since forever. Each year more male candidates apply for the midwifery departments at the medical universities. Aim. The aim of the article was to evaluate the perception of a male midwife by Warsaw hospitals’ patients. Material and methods. The research was performed on 350 female patients from 7 different Warsaw hospitals. Our own questionnaire was used. The statistical analysis was performed with Kruskal-Willis and median tests. The statistical importance factor was established: p < 0.05. Results and conclusions. The research proved that factors such as age, the size of the city of residence and the level of education are significant when it comes to the perception of a male midwife. The conclusions drawn from the results are as follows: male midwife has a chance for a professional success in patients’ opinion, factors such as age, the size of the city of residence and level of educations are important for male midwife perception, educating patients about benefits of the therapeutical relationship between male midwifes or male nurses are important tasks in nurses’ and midwifes’ work.